Debate made easy - Cleaver, Rodney; Wilson, Nancy Rabuck; Educational Video Network, Inc. (Huntsville, TX : Educational Video Network, Inc., 2001)
Being on a debate team cultivates intellectual curiosity and critical thinking capabilities, while it forces the student to consider two sides of an issue. This program discusses the two common debate formats, the Lincoln-Douglas debate and Cross-Examination debate. Also trains students to be part of an experience that will allow them to make their voice heard
Title from title screen
Executive editor, Anne Russell ; executive producer, George H. Russell ; videography, Rodney Cleaver, Shannon McWhirter, Jonathan Gillespie...[et al.] ; editor, Rodney Cleaver
Narrator: Judé L. Routh
Keywords: Debates and debating; Public speaking; Communication